2016
DOI: 10.1080/15384101.2016.1204059
|View full text |Cite
|
Sign up to set email alerts
|

Fidgetin-like 1 is a ciliogenesis-inhibitory centrosome protein

Abstract: Fidgetin-like 1 (FIGL-1) is a homolog of fidgetin, an AAA protein that was identified as the protein encoded by the gene mutated in fidget mice. Because the phenotypes of fidget mice are reminiscent of the phenotypes of ciliopathy diseases, and because fidgetin has microtubule-severing activity, we hypothesize that these proteins participate in cilia-related processes. Indeed, overexpression of FIGL-1 interfered with ciliogenesis in cultured cells. In particular, overexpressed FIGL-1 strongly accumulated at th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 39 publications
0
10
0
Order By: Relevance
“…VPS4 is a member of a family of AAA ATPase proteins that includes the microtubule severing proteins spastin, katanin and fidgetin 39 , which have also been shown to localize to centrosomes and spindle poles 40 43 . Disruption of the ESCRT-independent activity of VPS4 at the centrosome echoes phenotypes of disrupting activity of other AAA ATPase family members: a mutation that prevents katanin ATP hydrolysis reduces the volume of γ-tubulin at spindle poles 44 and changes in the expression levels and activity of fidgetin-like 1 affect ciliogenesis and alter the protein composition of the centrosome 45 . The shared evolutionary origins and similarity of the misregulation consequences at the centrosome raise the possibility that, like other members of the family, VPS4 at the centrosome could target microtubules.…”
Section: Discussionmentioning
confidence: 99%
“…VPS4 is a member of a family of AAA ATPase proteins that includes the microtubule severing proteins spastin, katanin and fidgetin 39 , which have also been shown to localize to centrosomes and spindle poles 40 43 . Disruption of the ESCRT-independent activity of VPS4 at the centrosome echoes phenotypes of disrupting activity of other AAA ATPase family members: a mutation that prevents katanin ATP hydrolysis reduces the volume of γ-tubulin at spindle poles 44 and changes in the expression levels and activity of fidgetin-like 1 affect ciliogenesis and alter the protein composition of the centrosome 45 . The shared evolutionary origins and similarity of the misregulation consequences at the centrosome raise the possibility that, like other members of the family, VPS4 at the centrosome could target microtubules.…”
Section: Discussionmentioning
confidence: 99%
“…Although there may exist essential and conserved function domains among FIGNL1s, molecular and biological functions of the AAA family members may have diverged among different species. For example, Zhao et al (2016) recently found that human FIGNL1 localizes at centrosomes, and is involved in ciliogenesis. Previous reports showed that C. elegans FIGNL1 binds to microtubules and controls mitotic progression in the germ line ( Luke-Glaser et al, 2007 ).…”
Section: Discussionmentioning
confidence: 99%
“…These MT-severing enzymes belong to the meiotic clade of the ATPases associated with diverse cellular activities (AAA+) superfamily together with their subsequently discovered paralogues, katanin-like 1, katanin-like 2, fidgetin-like 1 (Fignl1), and fidgetin-like 2 ( Hanson and Whiteheart, 2005 ; Yang et al, 2005 ; Roll-Mecak and McNally, 2010 ; Sharp and Ross, 2012 ). Among these paralogues, Fignl1 was shown to bind MTs in vitro and to participate in MT-dependent cellular processes such as mitosis ( Luke-Glaser et al, 2007 ) and ciliogenesis ( Zhao et al, 2016 ). However, its exact mode of action and its role in vertebrate nervous system development remained poorly explored.…”
Section: Introductionmentioning
confidence: 99%